The cognitive styles of satisfied decision support systems users: An hypothesis - Williams, Robert (McGraw Hill, 1999)
This paper presents an hypothesis for future testing to examine the relationship between user cognitive style and user satisfaction with Decision Support Systems (DSS). Preliminary research, in which subjects with different cognitive styles were found to have up to 17% difference in levels of satisfaction with a DSS, suggests the theoretical basis for the hypothesis. The DSS facilitated some users’ processes of consciousness, or ways of selecting and forming views of the world, more than others. Some types therefore experienced more satisfaction with the system because the computerised task engaged their most preferred cognitive processes, while other types were forced into their least preferred processes. DSS have certain common characteristic tasks, and it is hypothesised that such tasks will always lead to certain cognitive types experiencing higher satisfaction.